(untitled) - Hsu, Robert C. (Cambridge, Massachusetts, 1994)
This book defines basic concepts and terms from the Japanese economy. The only work of its kind in English, it is a convenient and comprehensive guide to all important economic and business aspects of dynamic postwar Japan. Topics include banks, major industries, corporate groups, financial systems, management practices, labor organizations, international trade and investment, and government economic policies. Over 150 topical essays, with comprehensive statistics, address major subjects. In addition more than 200 short definitional entries give translations and cross-references for important Japanese economic terms
Keywords: Japan,Nhật Bản; Economic conditions,Điều kiện kinh tế; 1945,1945